Tony Lowe and the Interdisciplinary and Critical Perspectives on Accounting Project. Issue 5 (2nd June 2014) - Laughlin, Richard
<x content-type="archive" xml:space="preserve">Abstract</x> Purpose – The purpose of this paper is to reflect on the life of Tony Lowe, Emeritus Professor of Accounting and Financial Management at the University of Sheffield, who died on 5 March 2014. It celebrates Tony Lowe's considerable direct contributions to accounting knowledge and, possibly more significantly, his indirect contribution through his enabling of a range of those associated with him at Sheffield to become scholars of distinction in their own right. Design/methodology/approach – Publication review, personal reflections and argument. Findings – Apart from providing insight into Tony Lowe's direct contribution to accounting knowledge through an analysis of a range of significant sole authored and joint authored publications, the paper gives rather more attention to his more indirect enabling contribution. In this regard it traces the development of initially the Management Control Association and subsequently the "Sheffield School" to Tony Lowe, clarifying the values that underlie these groups. It also clarifies how some of the key elements that have allowed the now global Interdisciplinary and Critical Perspectives on Accounting (ICPA) Project to exist and flourish are traceable to Tony Lowe and the "Sheffield School" he created. Research limitations/implications – This paper provides an important historical analysis of the direct and indirect influence of a unique scholar on the beginnings and development of particularly the now global ICPA Project. This history is personal and maybe selective and possibly limited because of this but hopefully will encourage others to investigate the claims further. Originality/value – The history of the ICPA Project has only partially been told before. This is another part of this history that has not been analysed before on which further work can build.